Penerapan Model Pembelajaran Problem Based Instruction untuk Meningkatkan Minat dan Hasil Belajar IPAS pada Siswa Kelas V SDN 03 Madiun Lor - Indartik, Indartik; Hanif, Muhammad; Sudarmiani, Sudarmiani (Universitas PGRI Madiun, 2024)
The aim of the research was to describe the implementation of problem based instruction in improving the achievement of science and social science of fifth grade students at 03 Madiun Lor Elementary School. The approach used was qualitative approach by using Classroom Action Researh. The research was done at 03 Madiun Lor Elementary School with the subject of research was the students of fifth grade for 7 months. The subjects was 27 students. The technique of collecting data used observation, questionnaire, and test. Data analysis used descriptive qualitative and quantitative. The result showed that the implementation of problem based instruction learning model could improve the learning motivation of the students in learning science and social science of fifth grade students at 03 Madiun Lor Elementary School. The improvement of the learning motivation in cycle 1 was 45,56% and cycle 2 was 92,59%. The improvement of average scores in cycle 1 was 74,81 and cycle 2 was 86,67. The research was terminated in cycle 2 because the target was achieved.Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaan problem based instruction dalam meningkatkan hasil belajar pada mata pelajaran IPAS SD pada siswa kelas V SDN 03 Madiun Lor. Pendekatan yang digunakan adalah pendekatan kualitatif dengan jenis penelitian tindakan kelas. Penelitian dilaksanakan di SDN 03 Madiun Lor selama 7 bulan. Subjek penelitian ini yaitu siswa kelas V yang berjumlah 27 siswa. Teknik pengumpulan data melalui observasi, angket, dan tes. Analisis data yang digunakan yaitu analisis deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penerapan model pembelajaan problem based instruction dapat meningkatkan minat dan hasil belajar IPAS siswa kelas V SDN 03 Madiun Lor. Peningkatan minat ditunjukkan dalam siklus 1 sebesar 45,56% dan siklus 2 sebesar 92,59% Sedangkan peningkatan rata-rata nilai hasil belajar pada siklus 1 sebesar 74,81 dan siklus 2 sebesar 86,67. Aktivitas riset dihentikan sampai pada siklus 2 karena target yang ditetapkan sudah terpenuhi.